Tax Incentive Analysis in The National Economic Recovery Program (PEN) - Dea Fitri Aulia (Social Impact Journal, 2022)
The purpose of this study is to find out how to provide tax incentives listed in the National Economic Recovery Program or PEN and to analyze whether a PEN policy has been successful or failed in its implementation. The existence of an unstable economy and social inequality as a result of the Laissez Faire doctrine in the 18th century where the government's role here was limited in the economic field caused Market Failure in the world. Thus, the government's role here is needed in order to overcome the market failure as well as to achieve economic efficiency and equity. One of the objectives of government equity is to perform a stabilization function, one of which is a state tax, which is one of the fiscal policies. In recent years, the Covid19 pandemiic storm has hit all countriies in the world, including Indonesian, causing a recession in the country's economy. In order to prevent entering the abyss of a deeper economic recession, the government in Indonesia has issued a policy which is summarized in the National Economic Recovery Program (PEN). The research method used is a liiterature study method, in which all data and information collected comes from journals, books or other sources which are then analyzed in depth. In general, the provision of tax incentives in the PEN program has a positive impact, this is evidenced by the surveys and evaluation studies conducted. Therefore, the policy of the national economic recovery program (PEN) carried out by the government in terms of providing tax incentives is deemed successful in its implementation.